METHODS THAT WORK: BEST PRACTICES OF ADULT EDUCATORS IN THE USA - Oksana Chugai; Olena Terenko; Olena Ogienko (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2017)
The article discusses best practices of American adult educators. The basic terms related to the topic, which are used in academic literature, are defined. Considering the range of terms synonymous to "adult educator" (teacher, instructor, trainer, practitioner, facilitator, mentor, educator, resource person, programme advisor, etc.), the roles adult educators play are described. The article concentrates on identifying the most important barriers to learning of adults (situational, dispositional, institutional, environmental, emotional) understanding of which is necessary for adult educators. Previous experience of adults is described as one of possible reasons for resistance to learning. The paper also reveals methods which adult educators use to overcome the barriers and facilitate adult learners in reaching their educational goals, the importance of flexibility for adult educators, providing choices for adults and ways of getting feedback. The eclectic approach to teaching adults, which may combine learner-centred teaching, content-centred teaching, reflective teaching, cooperative learning, experiential learning, and even traditional teaching, is found to be most appropriate. Thus, the article suggests considering the needs of adults, not adherence to a certain theory or approach, to be of utmost importance for adult educators. Best practices of American adult educators include: theory followed by practice, equal participation, team work, availability of choices, different types of assessment and reflection, which ensure practice, variety and enforcement.